Pretreatment level of circulating tumor cells is associated with lymph node metastasis in papillary thyroid carcinoma patients with ≤ 55 years old - Ming Yu; Jiaqin Deng; Yihua Gu; Yeqian Lai; Yuedong Wang (World Journal of Surgical Oncology)
Abstract Objective To investigate the relationship of pretreatment of circulating tumor cells (CTCs) and cervical lymph node metastasis (LNM) (central LNM (CLNM) and lateral LNM (LLNM)) in papillary thyroid carcinoma (PTC) patients with ≤ 55 years old. Methods Clinicopathological data (CTCs level, Hashimoto’s thyroiditis, thyroid function, multifocal, tumor size, invaded capsule, clinical stage, and LNM) of 588 PTC patients with ≤ 55 years old were retrospectively collected. The relationship of CLNM, LLNM and the clinical features of patients was analyzed. Univariate and multivariate logistic regression analyses were used to evaluate the relationship between the CTCs and CLNM, LLNM. Results There were 273(46.4%) and 89(15.1%) patients with CLNM and LLNM, respectively. Patients with CLNM had higher proportions of multifocality, tumor size > 1 cm, invaded capsule, and positive CTCs level than those without (all p < 0.05). Patients with LLNM had higher proportions of multifocality, tumor size > 1 cm, and invaded capsule than those without (all p < 0.05). Logistic regression analysis showed that multifocality (odds ratio (OR): 1.821, 95% confidence interval (CI): 1.230–2.698, p = 0.003), tumor size > 1 cm (OR: 3.444, 95% CI: 2.296–5.167, p < 0.001), invaded capsule (OR: 1.699, 95% CI: 1.167–2.473, p = 0.006), and positive CTCs level (OR: 1.469, 95% CI: 1.019–2.118, p = 0.040) were independently associated with CLNM; and multifocality (OR: 2.373, 95% CI: 1.389–4.052, p = 0.002), tumor size > 1 cm (OR: 5.344, 95% CI: 3.037–9.402, p < 0.001), and invaded capsule (OR: 2.591, 95% CI: 1.436–4.674, p = 0.002) were independently associated with LLNM. Conclusions Preoperative CTCs positive was associated with CLNM in PTC patients with ≤ 55 years old, but not LLNM.